Intestinal Growth in Glucagon Receptor Knockout Mice Is Not Associated With the Formation of AOM/DSS-Induced Tumors - Hunt, Jenna Elizabeth; Yassin, Mohammad; Olsen, Jørgen; Hartmann, Bolette; Holst, Jens Juul; Kissow, Hannelouise (Frontiers in Endocrinology, 2021)
Treatment with exogenous GLP-2 has been shown to accelerate the growth of intestinal adenomas and adenocarcinomas in experimental models of colonic neoplasia, however, the role of endogenous GLP-2 in tumor promotion is less well known. Mice with a global deletion of the glucagon receptor (Gcgr-/-) display an increase in circulating GLP-1 and GLP-2. Due to the intestinotrophic nature of GLP-2, we hypothesized that Gcgr-/- mice would be more susceptible to colonic dysplasia in a model of inflammation-induced colonic carcinogenesis. Female Gcgr-/- mice were first characterized for GLP-2 secretion and in a subsequent study they were given a single injection with the carcinogen azoxymethane (7.5 mg/kg) and treated with dextran sodium sulfate (DSS) (3%) for six days (n=19 and 9). A cohort of animals (n=4) received a colonoscopy 12 days following DSS treatment and all animals were sacrificed after six weeks. Disruption of glucagon receptor signaling led to increased GLP-2 secretion (p<0.0001) and an increased concentration of GLP-2 in the pancreas of Gcgr-/- mice, coinciding with an increase in small intestinal (p<0.0001) and colonic (p<0.05) weight. Increased villus height was recorded in the duodenum (p<0.001) and crypt depth was increased in the duodenum and jejunum (p<0.05 and p<0.05). Disruption of glucagon receptor signaling did not affect body weight during AOM/DSS treatment, neither did it affect the inflammatory score assessed during colonoscopy or the number of large and small adenomas present at the end of the study period. In conclusion, despite the increased endogenous GLP-2 secretion Gcgr-/- mice were not more susceptible to AOM/DSS-induced tumors.